Populational genomic insights of Paraclostridium bifermentans as an emerging human pathogen - Cai, Xunchao; Peng, Yao; Yang, Gongli; Feng, Lijuan; Tian, Xiaojuan; Huang, Ping; Mao, Yanping; Xu, Long (Frontiers in Microbiology, 2023)
Paraclostridium bifermentans (P.b) is an emerging human pathogen that is phylogenomically close to Paeniclostridium sordellii (P.s), while their populational genomic features and virulence capacity remain understudied. Here, we performed comparative genomic analyses of P.b and compared their pan-genomic features and virulence coding profiles to those of P.s. Our results revealed that P.b has a more plastic pangenome, a larger genome size, and a higher GC content than P.s. Interestingly, the P.b and P.s share similar core-genomic functions, but P.b encodes more functions in nutrient metabolism and energy conversion and fewer functions in host defense in their accessory-genomes. The P.b may initiate extracellular infection processes similar to those of P.s and Clostridium perfringens by encoding three toxin homologs (i.e., microbial collagenase, thiol-activated cytolysin, phospholipase C, which are involved in extracellular matrices degradation and membrane damaging) in their core-genomes. However, P.b is less toxic than the P.s by encoding fewer secretion toxins in the core-genome and fewer lethal toxins in the accessory-genome. Notably, P.b carries more toxins genes in their accessory-genomes, particularly those of plasmid origin. Moreover, three within-species and highly conserved plasmid groups, encoding virulence, gene acquisition, and adaptation, were carried by 25–33% of P.b strains and clustered by isolation source rather than geography. This study characterized the pan-genomic virulence features of P.b for the first time, and revealed that P. bifermentans is an emerging pathogen that can threaten human health in many aspects, emphasizing the importance of phenotypic and genomic characterizations of in situ clinical isolates.